Analisis Strategi Pembelajaran Soft Skill berbasis Media Sosial: Studi Kasus Perguruan Tinggi - Silmi Rizqi Ramadhani; Amalia Rahmah (Jurnal Informatika Terpadu, 2021)
In a college environment, the learning process consists of two ways. First, learning that uses hard skills emphasizes intellectual development that is directly on the problem. Second, soft skills learning. Lessons given while in college are more inclined to theoretical skills resulting in most students attach importance to hard skills in learning. Lack of soft skills education in students causes them to be only good at memorizing lessons and already feel successful by having skills. Students do not need not that hard skills, but both must run simultaneously. In soft skills education for students, it is usually taught face-to-face with teachers in universities. I am looking at the data of WeAreSocial.net and Hootsuite survey results as of January 2018, which states that Indonesia is the most significant active user of Instagram and Twitter in the world, the use of Instagram social media as a learning method can say as an opportunity that social media can also use for soft skills education, incredibly informal soft skills education such as character building. This study evaluates current soft skill education using the Likert scale formula. Then from the evaluation results can be a recommendation of soft skills education strategy for students using social media.